ajutati-ma va rog sa rezolv. 6-[( 6+6*6)-(6+6:6)]:7+6:6-6:6
Răspunsuri la întrebare
Răspuns de
1
6-[( 6+6*6)-(6+6:6)]:7+6:6-6:6=
6-[(6+36)-(6+1)]:7+1-1=
6-(42-7):7=
6-35:7=6-5=1
Raspuns: 1
6-[(6+36)-(6+1)]:7+1-1=
6-(42-7):7=
6-35:7=6-5=1
Raspuns: 1
wery:
multumesc.
Răspuns de
0
6-[(6+36)-(6+1)]:7+1-1=
6-(42-7):7+1-1=
6-35:7+1-1=
6-5+1-1=
1+1-1=
2-1=1
6-(42-7):7+1-1=
6-35:7+1-1=
6-5+1-1=
1+1-1=
2-1=1
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă